Admission Blood Pressure as Predictors of Thirty Days Mortality in Community Acquired Pneumonia in a Tertiary Care Hospital of Bangladesh (Journal of Medicine, 2025)
Background: Assessing admission blood pressure (BP) is crucial in predicting mortality community acquired pneumonia.Methodology: This was a prospective longitudinal study at DMCH to explore hemodynamic predictors of the 30-day all-cause mortality, including deaths during hospital stay and after discharge in community-acquired pneumonia. Statistical analyses included the Z-proportion test, multivariate logistic regression, and ROC curve analysis. A p-value of less than 0.05 was considered statistically significant.Results: The study's hospital mortality rate in community-acquired pneumonia was 14%. However, the all-cause mortality rate after 30 days of hospital admission increased to 22.6%. This was significantly associated with systolic blood pressure below 90 mmHg, diastolic pressure of 60 mm Hg or less, pulse of 40 mm Hg or less, and mean arterial pressure below 70 mm Hg (p